Endovascular Repair for Giant Right Subclavian Artery Aneurysm With Gore Viabahn and Pull-Through Procedure: A Case Report - Zha, Binshan; Chen, Zhiyong; Ou-yang, Huan (Frontiers in Surgery, 2022)
Abstract: Background: Giant true subclavian artery aneurysms (SAAs) (>5 cm) are rare. Technical and anatomical considerations complicate the endovascular treatment of SAAs and pose some challenges. Here, we present a giant right SAA that was successfully excluded using stent grafts with the pull-through technique after two interventional steps and discuss the pull-through technique details as well as the lessons to be learned from this case. Methods: A 50-year-old man presented at our department complaining of dyspnea and hoarseness. Computed tomography angiography (CTA) showed a giant right SAA with partial intraluminal thrombus and severe angulated aneurysm necks originating from the proximal right subclavian artery, approximately 70 × 71 mm in size. Outcomes: An 8 × 100-mm Gore Viabahn was selected to exclude the SAA. A decision was made to stabilize the wire tension using the pull-through technique. Final angiography showed that the SAA was essentially excluded, and slight endoleak was observed. At 6 months, imaging showed that the aneurysm was not obviously shrinking, there was still an endoleak and stent graft dislodgement was observed. Angiography confirmed a type Ia endoleak, which was managed by the placement of a 10 × 50-mm Gore Viabahn, again with the assistance of the pull-through technique. At the 25-month follow-up, CTA showed that the SAA was satisfactorily excluded, with no endoleak, and the SAA was reduced in size.